2018
DOI: 10.1016/j.apsusc.2018.06.226
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of barium titanate thin films as simple antireflection coatings for solar cells

Abstract: Barium titanate (BaTiO 3 , BTO) is a perovskite class material of remarkable dielectric, ferroelectric and ferromagnetic properties. Our previous studies on optical properties of BTO thin films proved high visible transmittance and sharp absorption edge at ~ 300 nm. Therefore the usage of BTO as a UV blocker or an antireflection (AR) coating in visible region is straightforward. AR coatings are agreed to be important parts of many photonic devices, among them also of solar cells. In this paper, single layers o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 31 publications
1
13
0
Order By: Relevance
“…The internal electric field is originated from the spontaneous polarization and domains of the materials themselves [1,3,5]. Photovoltaic effects have been many studied in ferroelectric perovskites including BiFeO3 [1,5], Pb(Zr,Ti)O3, Nd-doped BTO [7], BTO [2][3][4]8], and BST [9] where the current study reported efficiency of up to 21% [10].…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…The internal electric field is originated from the spontaneous polarization and domains of the materials themselves [1,3,5]. Photovoltaic effects have been many studied in ferroelectric perovskites including BiFeO3 [1,5], Pb(Zr,Ti)O3, Nd-doped BTO [7], BTO [2][3][4]8], and BST [9] where the current study reported efficiency of up to 21% [10].…”
Section: Introductionmentioning
confidence: 69%
“…It is a perovskite film sandwiched in a solar cell that acts as a photon absorber [1,2]. It is low production costs, high absorption coefficient of light, high mobility, and adjustable bandgap [3,4]. The photovoltaic effects in perovskite ferroelectrics occur inside the materials by exploiting the internal electric field to promote charge separation and electron transport [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Several methods to reduce the reflectance and enhance the efficiency of solar panels have been studied. Coating may be realized by both chemical and physical methods, such as sol–gel dip-coating 1 , spin coating 2 , nanoimprint lithography using sol–gel materials 3 , plasma surface oxidation 4 , RF sputtering 5 7 , and thermal evaporation 8 . In this work, we propose a simple and inexpensive sparking process to produce an AR film.…”
Section: Introductionmentioning
confidence: 99%
“…Among the contenders, perovskite BaTiO 3 (BTO), as a typical lead‐free displacement‐type ferroelectric featuring a large dielectric constant, stands out . Many researchers have investigated the functionalities of BTO thin film deposited on Si substrates, which not only can be used as a gate insulator, but also has other properties such as a rectifying effect, a photovoltaic effect, a room temperature luminescent effect, and an antireflection effect …”
Section: Introductionmentioning
confidence: 99%